Penerapan Program Boarding School dalam Pembentukan Karakter Religius Peserta Didik SMPIP Al-Madinah Cepogo - Hafidz; Luqyana Kautsar; Nurul Latifatul Inayat; Muhammad Nur Rochim Maksum; Triono Ali Mustofa (At Turots: Jurnal Pendidikan Islam, 2023)
This research is motivated by the condition of the religious character of SMPIP Al-Madinah Cepogo students who are still not in accordance with religious teachings, because there are still violations that are contrary to religious teachings that occur in the school environment, including there are students who have not carried out the obligation to pray  well, low etiquette towards teachers, lack of willingness to study religion, and low morals towards others.  One effort to repair this moral damage is to instill religious character in the younger generation through educational institutions.  The aims of this study are (1) to find out the application of the boarding school program in the formation of the religious character of SMPIP Al-Madinah Cepogo students.  (2) to determine the supporting and inhibiting factors for implementing the boarding school program in the formation of the religious character of SMPIP Al-Madinah Cepogo students.